Advances and challenges in therapeutic monoclonal antibodies drug development (Brazilian Journal of Pharmaceutical Sciences, 2018)
The use of serum containing polyclonal antibodies from animals immunized with toxins marked the beginning of the application of antibody-based therapy in late nineteenth century. Advances in basic research led to the development of the hybridoma technology in 1975. Eleven years later, the first therapeutic monoclonal antibody (mAb) was approved, and since then, driven by technological advances, the development of mAbs has played a prominent role in the pharmaceutical industry. In this review, we present the developments to circumvent problems of safety and efficacy arising from the murine origin of the first mAbs and generate structures more similar to human antibodies. As of October 2017, there are 61 mAbs and 11 Fc-fusion proteins in clinical use. An overview of all mAbs currently approved is provided, showing the development of sophisticated mAbs formats that were engineered based on the challenges posed by therapeutic indications, including antibody-drug conjugates (ADC) and glycoengineered mAbs. In the field of immunotherapy, the use of immunomodulators, bispecific mAbs and CAR-T cells are highlighted. As an example of promising therapy to treat infectious diseases, we discuss the generation of neutralizing monoclonal-oligoclonal antibodies obtained from human B cells. Scientific and technological advances represent mAbs successful translation to the clinic.